Philosophy Of Education In The Perspective Of Ecophenomenology: A New Approach To Sustainable Education - Nurfidah, Nurfidah; Fandir, A.; Rosdiyanti, Evi (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study explores the contribution of ecophenomenology in the philosophy of education to support sustainable education. By integrating the principle of the interconnectedness of humans and nature, direct experience through environmental- based learning, and critical reflection, this approach is able to increase students' ecological awareness and ethical responsibility. The results of the study indicate that ecophenomenology-based education can be an important tool in social transformation, although it still faces obstacles such as limited resources and policies. However, opportunities through green technology and environmentally friendly policies provide hope for building an education system that is more relevant and responsive to ecological challenges. This study emphasizes the importance of synergy between education, policy, and innovation to create a generation that is able to face global sustainability challenges holistically and sustainably.